If -3 is a zero of the polynomial (a – 1)x 2 + ax + 1, then find the value of a
Answers
Answered by
0
Answer:
I don,t know sorry I will not understand your question
Answered by
1
Answer:
Here's your answer
Step-by-step explanation:
Given = -3 is a zero of a polynomial
p(x) = (a - 1)x^2 + ax + 1
According to the question
p(-3) = (a - 1)(-3)^2 + a(-3) + 1 = 0
⇒(a - 1)9 - 3a + 1 = 0
⇒9a - 9 - 3a + 1 = 0
⇒9a - 3a - 9 + 1 = 0
⇒6a - 8 = 0
⇒6a = 8
⇒a = 8/6
⇒a = 4/3
Hope you understand .
Similar questions
Math,
1 month ago
Math,
1 month ago
Computer Science,
3 months ago
Math,
11 months ago
Math,
11 months ago